Social-Psychological Adaptation Of Syrian-Armenian Children Difficulties In Primary School Education Process - Lachinyan, Lilit; Sargsyan, Ani (Զանգակ հրատ.)
This article analyses and reveals the socio-psychological difficulties of adaptation of Syrian-Armenian children during elementary school educational activities. The effectiveness of social-psychological adaptation in the educational process is conditioned not only by the correct choice and application of educational programs, methods, means, but also by the pedagogues who implement the whole systematic educational process. The problem of the adaptation of Syrian-Armenian children in the educational process of primary classes can be called one of the most important problems of the school. It needs extensive research in terms of pedagogy and psychology and practical work in this direction. In order to study and identify the difficulties of adaptation in the educational process of Syrian-Armenian children, we have carried out research and corrective works from previously developed psychological tasks. The positive results of the research can be used to work with Syrian-Armenian children in educational institutions, reducing their social and psychological adjustment problems in the educational process.
Keywords: Psychology